Wear simulation of automotive engine component materials under biodiesel. - S.Y., Cetin; Md. Abdul, Maleque; Hassan, Masjuki; A., Hamdan (Universiti Malaysia Pahang, 2022)
Biodiesel has become increasingly common and significant alternative to traditional petroleum fuel in recent years. However, biodiesel has some adverse effects to the engine components materials. Therefore, in this study, wear simulation of automotive engine component materials was done using computational fluid dynamics approach to develop wear mechanism map. A pin-on-disc configuration was considered as a simulation model of wear under biodiesel using three different types of steel materials whereby load was applied from pin to disc during the simulation process. The relationship between wear rate, applied load and sliding velocity were simulated and discussed followed by a wear mechanism map. The corrosive and abrasive wear mixture were dominated for stainless steel, carbon steel and low-alloy steel. Stainless steel showed more wear-resistant behavior than other materials under biodiesel exposure. The individual wear map generated for the individual material is also discussed in the context of the wear mechanisms observed under biodiesel contact.